2022
DOI: 10.1186/s40885-021-00189-9
|View full text |Cite
|
Sign up to set email alerts
|

A complicated case of myocardial infarction with nonobstructive coronary arteries with an underlying pheochromocytoma: a case report

Abstract: Background The signs and symptoms of pheochromocytoma can imitate those of many other diseases, which may result in confusion. Therefore, diagnosing and treating secondary hypertension due to pheochromocytoma in deteriorating patients becomes challenging. Case presentation A 63-year-old female patient presented to the emergency room with severe and progressive nausea. The initial diagnosis was an acute myocardial infarction based on ST-segment depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Jung et al . [ 30 ] reported intracerebral hemorrhage, and Kissami et al . [ 31 ] reported intestinal bleeding.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Jung et al . [ 30 ] reported intracerebral hemorrhage, and Kissami et al . [ 31 ] reported intestinal bleeding.…”
Section: Resultsmentioning
confidence: 99%
“…We also identified that bleeding complications linked to dual antiplatelet therapy or heparin treatment is also a problem in MINOCA patients. There are cases showing gastrointestinal as well as intracerebral hemorrhage events [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NSTEMI-MINOCA presentations make up a significant proportion of all MINOCA cases. According to studies, patients with NSTEMI-MINOCA appeared more frequently than STEMI-MINOCA [ 2 , 29 - 30 ]. Angiographic criteria include the absence of obstructive disease on angiography (i.e., no coronary artery stenosis ≥50%) in any major epicardial vessel.…”
Section: Reviewmentioning
confidence: 99%